2012
DOI: 10.1016/j.joca.2011.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cartilage histopathology assessment systems on human knee joints at all stages of osteoarthritis development

Abstract: Objective To compare the MANKIN and OARSI cartilage histopathology assessment systems using human articular cartilage from a large number of donors across the adult age spectrum representing all levels of cartilage degradation. Design Human knees (n=125 from 65 donors; age range 23–92) were obtained from tissue banks. All cartilage surfaces were macroscopically graded. Osteochondral slabs representing the entire central regions of both femoral condyles, tibial plateaus, and the patella were processed for his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 28 publications
7
95
1
Order By: Relevance
“…Items for scoring were (i) cartilage structure (0-6), (ii) cartilage cells (0-3), (iii) Safranin O staining (0-4), and (iv) tidemark integrity (0-1).The modified Mankin's score range is from 0 to 14 and the higher the score, the more severe is the extent of osteoarthritis 20 .…”
Section: Histologic Studymentioning
confidence: 99%
“…Items for scoring were (i) cartilage structure (0-6), (ii) cartilage cells (0-3), (iii) Safranin O staining (0-4), and (iv) tidemark integrity (0-1).The modified Mankin's score range is from 0 to 14 and the higher the score, the more severe is the extent of osteoarthritis 20 .…”
Section: Histologic Studymentioning
confidence: 99%
“…Changes in articular cartilage include collagen disruption, PG depletion, and cell death 2,82 . Changes in subchondral bone include sclerosis [thickening, Fig.…”
Section: Hiu As a Surgical Toolmentioning
confidence: 99%
“…Changes in subchondral bone include sclerosis [thickening, Fig. 4] and changes in joint anatomy include the formation and development of osteophytes 2,14 . Osteophytes that restrict joint mobility are often removed surgically 1,83 .…”
Section: Hiu As a Surgical Toolmentioning
confidence: 99%
“…Second, previous work regarding scoring joints for OA severity have suggested that cellularity and tidemark cause the most scoring discrepancy and need more consensus and/or better illustrations [40]. Our study provides a more clear illustration of the correlation of the tidemark and calcification under a variety of OA severities.…”
Section: Discussionmentioning
confidence: 68%